A revision of the genus Belciana Walker, 1862 with description of three new species (Lepidoptera, Noctuidae: Pantheinae) from East and South East Asia. Revision of Pantheinae, contribution XII - Behounek, G.; Han, H.l.; Kononenko, V.s. (Zootaxa, 2015)
The Oriental Pantheinae genus Belciana Walker, 1862 is revised. Three new species, B. hreblayi sp. n., B. sulawesiana sp. n., B. pinratanai sp. n., from Taiwan, Indonesia and Thailand, are described. Five new combinations in the genus Diphteroides Bethune-Baker, 1906 are proposed: Diphteroides caerulea (Hampson, 1926) comb. n., D. habroscia (Prout, 1924) comb. n., D. patricolor (Prout, 1924) comb. n., D. serrata Bethune-Baker, 1906, D. subserrata (Prout, 1924) comb. n. and D. sophronia (Prout, 1924) comb. n. The extensive diagnoses of known species of Belciana are given. The imagines, male and female genitalia are illustrated. The checklist of the genus Belciana in East Asia is presented.